Process modifications to maximise energy savings in total site heat integration - Kew, HongChew (Elsevier Limited, 2015)
This paper extends the scope of the Pinch Analysis for process modifications of individual processes to total site heat integration (TSHI). The Plus-Minus principle has been adapted to enable the beneficial process modification options to be selected in order to maximise energy savings in TSHI. The Total Site Profile (TSP) is divided into three regions: (a) the region above the horizontal overlap between the Site Sink and Source Profiles, (b) the horizontal overlap region and (c) below the horizontal overlap region. The proposed methodology identifies the options to reduce utility targets in these regions using the TSP, Site Utility Composite Curves (SCC), Utility Grand Composite Curve (UGCC), modified Problem Table Algorithm (PTA), Total Site Problem Table Algorithm (TS-PTA) and some new heuristics. The identified changes on the TSP are then linked to the specific changes at the individual processes. The illustrative case study shows that the Plus-Minus principle application in the TSHI context can further improve heat recovery. The proposed spreadsheet-based methodology combines the advantages of graphical visualisation, as well as the numerical precision.